Externalizing behavior problem among children age four and below in Peninsular Malaysia - Ahmad, Nor Fairani; Mansor, Mariani (Leena & Luna International (Pvt) Limited, 2016)
This paper aims to examine the rates and distribution of externalizing behaviour problems and to identify associated children and parental characteristics that affect externalizing behaviour problems among preschool children in Peninsular Malaysia. A total of 174 (14.5%) out of 1198 children age four and below were conveniently selected for this study that consist of those who were in the borderline and clinical range of having externalizing behavioural problems as rated by parents using the Child Behavioural Checklist for Age 1 ½-5 (CBCL/1 ½ – 5). Descriptive statistics such as mean, t-test, ANOVA and correlation tests were applied in data analysis. Findings indicate significant differences in externalizing problem by age until age 4 and maternal education background. Results reveal a negative but non-significant correlation between externalizing problems with household income and father’s age, whilst a positive with moderate significant relationship with child age. Findings in this study provide an increased knowledge in externalizing behaviour problems and adequate evidences that early intervention or preventive measure is needed to reduce the continuity of externalizing problems into adulthood and preschool age is the best time to identify early signs of problems before they become permanent.